Systematic Literature Review: Peluang Digitalisasi dalam Pengembangan Akuntansi Syariah - Windah Windah (Journal of Economics, Management, and Accounting, 2026)
The development of digital technology has driven transformation across various sectors, including Islamic accounting, which is required to adapt to changes in the modern business environment. This study aims to analyze the opportunities of digitalization in the development of Islamic accounting and identify digital technologies that support its transformation. The research employs a Systematic Literature Review (SLR) method through the stages of search process, inclusion and exclusion criteria, and quality assessment. The literature was obtained from Google Scholar within the publication period of 2022–2026, resulting in 15 initial articles, 10 articles passing the screening stage, and 7 articles meeting the quality criteria. The findings indicate that digitalization improves efficiency, transparency, accountability, reporting quality, service innovation, and access to Islamic financial services. A total of 14 categories of digital technologies were identified, with blockchain, artificial intelligence, Islamic fintech, cloud computing, and big data analytics as the most dominant technologies. Digitalization plays an important role in supporting a more adaptive and sustainable transformation of Islamic accounting.